Direct observation of spin-forbidden transitions through the use of suitably polarized light - Lévêque, Camille; Peláez, Daniel; Köppel, Horst; Taïeb, Richard (Nature Communications, 2014)
The study of excited triplet states of a molecular system is a difficult task because accessing them involves forbidden transitions from the singlet ground state. Nevertheless, absorption spectra of many molecules present, at low energies, the weak fingerprint of these triplet states. At higher energies this information is usually masked by the intense signal of the singlet states. Here we show, for the specific case of the sulphur dioxide molecule, that the combined use of polarized light and molecular alignment can enhance the triplet part of the spectrum, even making it the only absorption process.